Perkembangan surat kabar dalam pusaran politik: Kajian surat kabar Sinar Harapan 1961 – 1986 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research aimed to conduct an in-depth study of the dynamics of newspaper development during the transition of the Soekarno government to Suharto. On its way as a newspaper, it found some restraint until the revocation of the issuance license because it was considered not in line with the government’s goals at that time. In general, this study wants to answer the question of “how is the dynamics of newspaper travel in the period of authoritarian rule, especially Sinar Harapan newspaper in Indonesia?”. To test the problem, researchers conducted the study using historical methods that included four steps of research. Research steps include the collection of written sources through the study of literature (heuristics), criticism of sources, interpretation or analysis of sources, and historiography. Researchers also use concepts to simplify the analysis, including newspapers, authoritarians, politics, government. A rationalization for the study of this newspaper, due to the many perspectives on the claims made by the government or the newspaper itself. The analysis of authoritarian theory appears in the form of accountability for newspaper analysis as an object of historical immersion. The theory of the authoritarian press is used as an analysis of the dynamics of newspaper development in Indonesia.
Keywords: Authoritarian; Government; Newspapers